Effect of three treatments on the seminal filancia and its relationship with sperm quality in alpacas (Vicugna pacos) - Ramírez R., Andrés A. (2021)
The aim of this study was to evaluate the effect of collagenase, pipetting and incubation to reduce the filancia of semen and its relationship with sperm quality in alpacas for its cryopreservation. Semen samples were obtained by artificial vagina from 4-7-year-old males at the Reproductive Biotechnology Laboratory of the Canaán Agrarian Experimental Station of INIA (Ayacucho, Peru). The macroscopic (volume, pH and filancia) and microscopic (motility, concentration and vitality) characteristics of the semen were evaluated. Each sample was distributed in three aliquots and diluted with the commercial AndroMed® extender in a 1:1 ratio at 37 °C and subjected to three treatments: T1 = Collagenase 5%; T2 = Pipetting 10 times, and T3 = Incubation at 37 °C for 10 min. The microscopic characteristics were evaluated at 0, 20, 40, 60 and 120 min post-dilution). The filancia decreased significantly from 0.95, 0.89 and 0.91 cm to 0.26, 0.27 and 0.33 cm at 120 min post-dilution for T1, T2 and T3, respectively (p<0.05), but without differences between treatments. Sperm motility and vitality were not affected by post-dilution times, but motility decreased significantly (p<0.05) after semen dilution. It is concluded that the use of collagenase, pipetting, and incubation decreased the filancia of post-dilution alpaca semen, affecting sperm motility and vitality.